Pediatric Radiation Oncology (Pediatric Oncology,, 2018)
This book presents the most up-to-date and innovative information on the targeting and treatment of a wide range of childhood cancers by means of radiation therapy. Written by global experts in pediatric radiation oncology, it documents in detail the treatment regimens appropriate to each disease, highlighting the recent advances that promise to improve rates of survival and cure. The use of image-guided and intensity-modulated radiation therapy is clearly described, and careful attention is also devoted to the roles of proton therapy, stereotactic radiosurgery, stereotactic fractionated radiosurgery, and modulated arc radiotherapy. Separate chapters address localization and verification procedures and anesthesia; pediatric radiation oncology in the palliative care setting; and aspects that are especially relevant in low- and medium-income countries. Beyond clinical radiation oncology, relevant information is provided on radiation physics. The book concludes by examining future directions in the field.